ANALYSIS OF VARIABLES AFFECTING LABOR ABSORPTION IN THE WOOD CRAFT INDUSTRY IN GIANYAR DISTRICT - I Gusti Putu Agung Masguhyantara; Ni Putu Martini Dewi (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
Labor absorption is the number of jobs that have been filled, which is reflected in the number of working people. The working population is absorbed and spread across various sectors of the economy. Gianyar Regency is known for its variety of souvenirs, one of which is a variety of wood craft industry centers. Through labor absorption, it can show the ability of a company to absorb a number of people to produce a product and increase production value. However, the wood craft industry in Gianyar Regency has an imbalance in labor absorption. The objectives of this study are: 1) To analyze the simultaneous influence of wages, education, capital, and sales turnover on the absorption of wood craft industry labor in Gianyar Regency, 2) To analyze the partial effect of wages, education, capital, and sales turnover on the employment of the wood craft industry in Gianyar Regency. This research was conducted in Gianyar Regency with a total of 476 wood craftsmen business units. The object of this research is the owner of the wood industry in Gianyar Regency. The sample in this study amounted to 83 respondents. The methods used include observation, structured interviews, and questionnaire methods. Based on the results obtained, it shows that 1) wages, education, capital, and sales turnover simultaneously have a significant effect on labor absorption 2) wages, education, capital, and sales turnover partially have a positive and significant effect on labor absorption in the wood industry in Gianyar Regency.